First multivisceral transplantation in Mitchell‐Riley/Martinez‐Frias syndrome. (20th March 2022) - Estefanía‐Fernández, Karla; Andrés, Ane; Alcolea, Alida; Velayos‐López, María; Pastrían, Laura G.; Ramírez‐Amorós, Carla; Gonzalez, Rocío; Sarría, Marta; Ramos, Esther; López‐Santamaria, Manuel; Hernández, Francisco
Abstract: Background: MRS/MFS is a rare multisystem disorder with a poor prognosis. The high mortality rate of this syndrome is related to the severity of the associated gastrointestinal, pancreatic, and hepatobiliary conditions, as most of them are not amenable to conventional medical and surgical treatments. Methods: We report the case of a Romani girl with all the key clinical features of MRS/MFS, and a review of cases reported in the literature. Our patient is a newborn from consanguineous parents who presented duodenal atresia, hypoplastic pancreas, gallbladder agenesis, and neonatal diabetes. Given the clinical suspicion of MRS/MFS, a genetic analysis was performed which revealed the presence of a homozygous variant in the RFX6 gene. During the course of the disease, the patient presented intractable secretory diarrhea and severe intestinal failure. Results: At 2 years of age, she underwent MVT of the stomach, duodenum, small intestine, colon, liver, and pancreas. There were no surgical complications. Histologic evaluation of the small bowel showed extensive patches of gastric heterotopia. After more than 10 years of follow‐up, she had presented with normal gastrointestinal, hepatic, and pancreatic function. She has one of the longest survival periods in the literature. Conclusions: Our experience suggests that multivisceral transplantation may be a promising option in select cases of MRS/MFS.